Cutting Performance of Microcrystalline, Nanocrystalline and Dual-Layer Composite Diamond Coated Tools in Drilling Carbon Fiber Reinforced Plastics - Jianguo Zhang; Yigao Yuan; Jinjiang Zhang (Applied Sciences, 2018)
The drilling of carbon fiber reinforced plastics (CFRP) is a significant topic for the aircraft industry. However, CFRP are materials which are difficult to cut due to their unique properties. This paper studies tools with excellent cutting performance in machining CFRP. The microcrystalline diamond (MCD), nanocrystalline diamond (NCD), and dual-layer composite MCD/NCD coatings are deposited on Co-cemented tungsten carbide (WC-Co) drills. The morphology of MCD shows pyramidal grains and the NCD and MCD/NCD coatings present cauliflower-like morphology. The cutting performances of coated tools are checked in CFRP drilling tests by the drilling force and tool wear. According to the results, the dual-layer composite MCD/NCD coated tools present the best cutting performance with the lowest drilling force. Meanwhile, the MCD/NCD coated tools display high resistance to wear and adhesive strength.